Separation Processes in the Food and Biotechnology Industries - Grandison, A.S. (Woodhead Publishing, 2011)
This book reviews recent methods and techniques for separating food components and products of the biotechnology industry. The introduction focuses on food composition and some of the conventional separation techniques.